Evaluation of Water Availability in Batukarut to Fulfill Irrigation Water Needs in Batukarut and Clean Water PDAM Sukabumi City - Mustopa, Ali; Hartono, Hartono; Robial, Siti Muawanah (Universitas Negeri Semarang, 2024)
The condition of water availability in the Batukarut area is unstable in meeting clean water and irrigation needs, so there is a need for further analysis in fulfilling clean water and irrigation. The aim of this research is to determine the conditions of water availability, determine the amount of clean water needed and irrigation needs and the distribution of water when there is a shortage. The method used to determine water availability is the FJ Mock (1973) method with the water balance principle. The research results show that water availability in Batukarut using Q 90%, the maximum discharge occurs in February with a value of 231.5 liters/second and the minimum value occurs in September and October with a value of 87.3 liters/second. PDAM Tirta Bumi Wibawa Sukabumi's clean water requirement is 150 liters/second. Regarding water requirements for irrigation, the maximum requirement occurs in May with a discharge of 414.4 liters/second, while the minimum requirement occurs in November with a value of 0.00 liters/second. The distribution of water needs in February requires clean water of 150 liters/second and irrigation needs of 87.3 liters/second, the distribution of water needs in October of clean water needs of 50 liters/second, irrigation needs of 37.3 liters/second.